Abdominal vascular injuries- what general/ trauma surgeons should know - Zia Ur Rehman (Journal of the Pakistan Medical Association, 2021)
Abdominal vascular injuries are the common cause of death after abdominal trauma. These are challenging injuries to manage due to severe haemodynamic instability, associated injuries and difficulty in accessing and controlling these vessels. Early control of bleeding can decrease the mortality in these patients. Abdominal vasculature is divided in four zones and each zone need different operative strategy for exposure. Principles of proximal and distal control are followed before exploring any haematoma. Endovascular interventions (angioembolization, stent-graft) have shown improved outcomes in patients with blunt abdominal trauma. Resuscitative Endovascular Balloon Occlusion of Aorta is minimal invasive method of achieving aortic occlusion and acts as bridge for definitive intervention or surgery. Updated knowledge is necessary for all those directly involved in managing these patients. The current review discusses relevant anatomy, principles, different surgical approaches and endovascular techniques to deal these injuries. Keywords: Abdominal trauma; injury; aorta; inferior vena cava. Continuous....